Income Distribution, Inflation and Economic Growth: A Post-Keynesian Approach - Amitrano, Claudio Roberto; Vasconcelos, Lucas (Panoeconomicus, 2019)
The dispute between social classes for fractions of income was a central theme for economic analysis at least since David Ricardo and Karl Marx. Its importance as an interpretative key declined with the marginalist revolution of the late nineteenth century and did not regain its central role in the conventional economic approach ever since. However, its relevance was maintained among heterodox economists such as Michal Kalecki and reinvigorated by post-Keynesian thinking. This paper seeks to offer three analytical contributions to the post-Keynesian literature: (1) it presents an integrated framework on the relationship between distributive conflict, inflation and economic growth in an open economy with government; (2) it proposes the use of a general framework, based on liquid preference, assets own interest rates, currency hierarchy and productivity differentials to understand the determinants of the spot exchange rate; and (3) it suggests a distinct monetary rule to take into account the role of interest rates on distributive conflict inflation and demand and growth regimes. Key words: Income distribution conflict, Exchange rate, Inflation, Economic growth. JEL: E12, E25, E31, O41. Distribucija dohotka, inflacija i ekonomski rast: postkejnzijanski pristup Sukob između društvenih klasa za delove dohotka bio je centralna tema ekonomske analize barem od Davida Ricarda i Karla Marksa. Njegov značaj kao interpretativnog ključa opao je sa marginalističkom revolucijom krajem devetnaestog veka i od tada nije povratio svoju centralnu ulogu u konvencionalnom ekonomskom pristupu. Međutim, njegova relevantnost je zadržana među heterodoksnim ekonomistima kao što je Michal Kalecki i oživljen je post-kejnzijanskim razmišljanjem. Ovaj rad nastoji da ponudi tri analitička doprinosa post-kejnzijanskoj literaturi: (1) predstavlja integrisani okvir o odnosu između distributivnog konflikta, inflacije i ekonomskog rasta u otvorenoj ekonomiji sa Vladom; (2) predlaže upotrebu opšteg okvira, zasnovanog na preferencijama likvidnosti, kamatnim stopama sopstvenih kamata, hijerarhiji valute i razlikama u produktivnosti da bi se razumele determinante deviznog kursa; i (3) sugeriše posebno monetarno pravilo da se uzme u obzir uloga kamatnih stopa na inflaciju distributivnog konflikta i režime potražnje i rasta. Ključne reči: Konflikt distribucije prihoda, devizni kurs, inflacija, ekonomski rast.